Acceptability of Intrauterine Contraceptive Device Insertion in immediate Postpartum Period - Zunaira Arshad, Shahid Hassan Anjum, Faiza Iqbal, Shabnam Tahir, Anam Saqib, Sahrish Gul (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Mostly, females seek birth space after a delivery. But usually are unaware about contraceptive method and their usage, especially during postpartum period. Controversial results have been noticed from literature regarding the acceptability of PPIUCD among females of reproductive age groups. So we conducted this study to find the acceptability in local population. Aim: To determine the frequency of acceptability of immediate post-partum intra-uterine contraceptive device insertion in females presenting for delivery. Methods: This cross sectional study was conducted in Gynae Unit-II, Shalamar Hospital, Lahore for a period of six months after approval of synopsis i.e. from 4th October 2016 to 4th April, 2017. 90 patients enrolled in this study. Informed consent was taken from all the patients. After delivery, IUCD implanted after taking approval from female and her husband and acceptability noted. All the collected data was entered and analyzed on SPSS version 20. Results: The mean age of the patients was 29.52±7.38 years. The low SES patients were 41(45.6%), middle SES patients were 40(44.4%) and high SES patients were 9(10%). In this study 54(60%) patients accepted the use of IUCD. Conclusion: In our study, the acceptability of immediate PPIUCD insertion in females presenting for delivery was 60%.